Symmetry aspects of chiral superconductors. Issue 2 (3rd April 2022) - Ramires, Aline
Abstract : Recent developments in theory, synthesis, and experimental probes of quantum systems have revealed many suitable candidate materials to host chiral superconductivity. Chiral superconductors are a subset of unconventional superconductors which break time-reversal symmetry. Time-reversal symmetry breaking is possible given the order parameter's two-component nature, allowing for a complex relative phase. In this article, we focus on discussing the underlying symmetry aspects that allow for the development of chiral superconductivity. We provide an introductory account of key concepts in group theory and apply these to the classification of order parameters and the generalization of the Landau theory of phase transitions in the context of superconductivity.